Sonophotocatalytic Degradation of Alizarin Red: Reactive Dye Over Slurry Titanium Dioxide - Sangwan, Pratibha (My University, 2009)
The release of dyes into the receiving water bodies is deleterious, not only because of their color, but also because they are not easily degraded by aerobic bacteria and forms toxic compounds under the action of anaerobic bacteria. Therefore, it becomes imperative to completely degrade these organic compounds before their discharge. Such pollutants cannot be completely degraded by well established techniques like coagulation, flocculation, precipitation, adsorption, membrane separation, aerobic biological treatment. The incapability of conventional wastewater treatment methods to effectively remove such pollutants leads to explore the new, efficient and cost effective treatment systems. In order to meet stringent environmental regulations, the latest development is the oxidation of these biorecalcitrant organic compounds. These radicals have high oxidizing power superior to other usual oxidants and results in complete degradation. The methods are called advanced oxidation processes (AOP’s),which are characterized by production of the hydroxyl radical (OH) as a primary oxidant. Examples of AOP’s include the use of (H2O2/UV), semiconductor photocatalysis, ozonolysis and ultrasonic irradiation (sonolysis), (ultrasound/O3) as important segmental or parallel processes and are found to enhance OH radical production leading to higher oxidation rates and organic matter mineralization. In this work, we investigated the Photocatalytic oxidative degradation and discoloration of various reactive dyes and dye intermediates using light (UV/visible)/semiconductor catalyst by optimizing the operational parameters to ensure the rapid and complete transformation of the toxic organic compounds to benign chemicals. Also the simultaneous sonochemical effect along with photochemical oxidation process light/semiconductor/ultrasound) is used which leads to faster destruction rate. The scope of this project is to see Sonophotocatalysis as a viable treatment option in case of dyes. Titanium dioxide was used as Photocatalyst. Experiments were performed in slurry mode in both UV and solar light at optimized condition. The degradation of wastewater has been investigated in terms of reduction in Conc. Various process parameters like catalyst dose, pH, concentration of oxidant, initially pollutant concentration were varied and their effects have been analyzed. In this case the catalyst concentration was optimized at .1g/200ml, pH at 4.8 and oxidant concentration at 3ml/200ml of the sample. The results obtained were quit appreciable as it reduced COD from 240 to 80 mg/l, BOD from 80% mg/l. The results of Sonophotocatalytic degradation of dyes showed that it could be used as efficient and environmental friendly technique for the complete degradation of recalcitrant organic pollutants which will increase the chances for the reuse of wastewater. The investigations demonstrate the importance of selecting the optimal degradation parameters for practical applications of this operation.
Keywords: Sonophotocatalytic; Dye; Titanium Dioxide